Pengembangan LKPD Berbasis Kooperatif Tipe STAD untuk Melatihkan Keterampilan Kolaborasi pada Tema 7 Subtema 1 Kelas III Sekolah Dasar - Ayu Amelia; Bagus Rahmad Wijaya (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this development research was to determine the validity, practicality, and effectiveness of STAD type cooperative-based worksheets to train collaboration skills on theme 7 sub-theme 1 class III elementary schools. The research model used is 4D. Based on expert validation, the following percentages were obtained: 97% learning design experts with very valid criteria, 90.6% content/material experts with very valid criteria, and 98% teaching materials experts with very valid criteria. The practicality of LKPD was obtained from the results of teacher observations in using the product by 93.3% with very practical criteria and the results of student observations in using the product by 96.2% with very practical criteria. The effectiveness of LKPD was obtained from the results of observations of collaboration skills of 97.1% with very collaborative criteria and the results of the teacher and student response questionnaires after using the product were 95.8% with very good criteria. Based on the results of the research conducted, the STAD-type cooperative-based LKPD for training collaboration skills on theme 7 sub-theme 1 class III elementary schools can be said to be valid, practical, and effective so that it is feasible to use..